Gamification and MDA framework: conceptual model to promote motivation in the elderly - Pinho, Anabela (2020)
Longevity with quality of life is a converging ideal with assumptions in health promotion. From this premise results the importance of a study where possible combinations are found using strategies and technological tools in order to build models that create motivation in people, especially in the elderly to perform healthy practices that allow them to well-being and active ageing. The creation of strategies that motivate the adoption and use of these technologies by the elderly becomes challenging. In turn, technological development has given rise to new tools, and with them,new behaviors in people's lives. Games are a good example, enhancers of engagement, commitment and behavior change. The most recent phenomenon is gamification, which emerges as a catalyst for motivation. The current research aims to propose a model to enhance the motivation in the elderly to perform certain tasks. It is a conceptual model built through the application of gamification based on the Mechanics, Dynamics, Aesthetics (MDA) framework. Its development resulted from a systematic work that focused on a review of what was done in terms of gamification application and how gamification strategies were used having as support the MDA framework. This article presents the steps developed in the construction of the proposed model, from literature review, gamification application and MDA framework utilization.